Effect of addition of ceramic granules on compressive Strength Concrete - Srie Gunarti, Anita Setyowati; Paiyati, Ninik; Ningrum Aflfandi, Ratna (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2010)
Future technological developments are now demanding concrete action to improve the performance of concrete produced, both in terms of quality, materials and how to apply, it is not free from the demands and needs of the community towards a more advanced infrastructure facilities. It is therefore necessary to find an alternative as the base material is replaced with a grain of sand concrete waste ceramics. Attempts to utilize the waste form ceramic grains will not only reduce environmental problems but it can provide economic value for development, as well as efforts to conserve natural resources. The study was conducted at the Concrete Laboratory of the University of Islam "45" Bekasi using the IS and ISO standards, the quality of K-175 concrete plans. Level of addition of ceramic granules 0%, 5%, 10%, 15%, 20% of the weight of sand. Press firmly on the treatment of testing performed on concrete specimens at the age of seven days, 14 days, and 28 days. The test results of concrete compressive strength at 28 days of treatment, showed normal concrete compressive strength (•without mixture of ceramic granules^ is 187.21 kg/cm2. There was a decrease the value of concrete compressive strength of concrete on the ceramic granules are added to the mixture of 5% is 147.99 kg/cm2, the mixture of 10% is 140.08 kg/cm2, the mixture of 15% is 131.40 kg/cm2, the mixture of 20% is 124.43 kg/cm2.